Internalizing symptoms and polyvictimization in a clinical sample of adolescents: The roles of social support and non-productive coping strategies. (April 2016) - Guerra, Cristóbal; Pereda, Noemí; Guilera, Georgina; Abad, Judit
Abstract: Given the high prevalence of internalizing disorders during adolescence, it is necessary to determine the factors influencing their development and evolution. The aim of this study was to evaluate the role of polyvictimization in developing internalizing symptoms while considering the possible effect of non-productive coping and the availability of social support. The participants were 144 adolescents ( M  = 14.31, SD  = 1.48) cared for in child and adolescent mental health services. The results of multiple regression analysis indicated that polyvictimization, non-productive coping and social support were good predictors of internalizing symptoms. In addition, non-productive coping acted as a mediator in the relationship between polyvictimization and internalizing symptoms. The results of the study emphasized the importance of the studied factors to understanding the process of development internalizing symptoms and to preventing or treating adolescents who suffer from these types of disorders.